Advances in the Diagnosis of Venous Thromboembolism: A Literature Review - Harish Patel; Haozhe Sun; Ali N. Hussain; Trupti Vakde (Diagnostics, 2020)
The incidence of venous thromboembolism (VTE), including lower extremity deep vein thrombosis (DVT) and pulmonary embolism (PE) is increasing. The increase in suspicion for VTE has lowered the threshold for performing imaging studies to confirm diagnosis of VTE. However, only 20% of suspected cases have a confirmed diagnosis of VTE. Development of pulmonary embolism rule-out criteria (PERC) and update in pre-test probability have changed the paradigm of ruling-out patient with low index of suspicion. The D-dimer test in conjunction to the pre-test probability has been utilized in VTE diagnosis. The age appropriate D-dimer cutoff and inclusion of YEARS algorithm (signs of the DVT, hemoptysis and whether PE is the likely diagnosis) for the D-dimer cutoff have been recent updates in the evaluation of suspected PE. Multi-detector computed tomography pulmonary angiography (CTPA) and compression ultrasound (CUS) are the preferred imaging modality to diagnose PE and DVT respectively. The VTE diagnostic algorithm do differ in pregnant individuals. The prerequisite of avoiding excessive radiation has recruited planar ventilation-perfusion (V/Q) scan as preferred in pregnant patients to evaluate for PE. The modification of CUS protocol with addition of the Valsalva maneuver should be performed while evaluating DVT in pregnant individual.